Political cycles in Latin America: More evidence on the Brazilian economy - Celso José Costa Júnior; Alejandro García-Cintado; Manuel Alejandro Hidalgo (Latin American Economic Review, 2021)
This paper aims to shed additional light on the existence of opportunistic and partisan political-business cycles in the Brazilian economy over the 1996-2016 period. To that end, it relies on two different approaches: (I) an Oaxaca model in the spirit of Blinder and Watson (2016); and (II) a DSGE model where fiscal and monetary policies are treated as political- regime dependent (Milani, 2010). By and large, our results from both exercises show that there existed an opportunistic behavior by all the governments studied as regards fiscal policy, and that political ideology played a role in shaping macroeconomic policies in some of the administrations that ran the country within the time span considered. Specifically, as our DSGE exercise illustrates, President Dilma Rouseff's fiscal management differed significantly from previous governments'. In addition, we do not find any evidence of political business cycle of any type when it comes to monetary policy, in line with what the consensus in this literature states for the case of Brazil.
Keywords: D72; E32; E52; E58; E62; 330; Political cycles; monetary policy; fiscal policy; Oaxaca model; Dynamic Stochastic General Equilibrium (DSGE) model